2015
DOI: 10.1590/s0102-6720201500040012
|View full text |Cite|
|
Sign up to set email alerts
|

Immunological Evaluation of Patients With Type 2 Diabetes Mellitus Submitted to Metabolic Surgery

Abstract: Background : Immunological and inflammatory mechanisms play a key role in the development and progression of type 2 diabetes mellitus. Aim : To raise the hypothesis that alterations in immunological parameters occur after duodenojejunal bypass surgery combined with ileal interposition without gastrectomy, and influences the insulin metabolism of betacells.Methods : Seventeen patients with type 2 diabetes mellitus under clinical management were submitted to surgery and blood samples were collected before and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…An alternative hypothesis involves rapid delivery of ingested nutrients not absorbed by the distal intestine, which would increase the secretion of GLP-1 4 , 27 . Although the mechanism for this effect is not completely known yet, it can be directly related with the change in the flow of nutrients, despite any effect in the secretion of known or hypothetical intestinal hormones.…”
Section: Resultsmentioning
confidence: 99%
“…An alternative hypothesis involves rapid delivery of ingested nutrients not absorbed by the distal intestine, which would increase the secretion of GLP-1 4 , 27 . Although the mechanism for this effect is not completely known yet, it can be directly related with the change in the flow of nutrients, despite any effect in the secretion of known or hypothetical intestinal hormones.…”
Section: Resultsmentioning
confidence: 99%
“…Sigalet et al (36) also revealed that pediatric patients with active Crohn's disease presented significantly lower postprandial GLP-2 levels than healthy controls. Although the inflammation is supposed to be much more intense in inflammatory bowel diseases, obesity and T2D are also associated with a low-grade chronic inflammatory state (37)(38)(39)(40) . In fact, the discrepancy in CRP levels among the groups along with the differences in the GLP-2 levels observed in the present study tend to signal that this inflammatory state may also play a significant role in this mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Thiazolidinediones improve insulin sensitivity while sulfonylureas stimulate the secretion of this hormone [11] . In contrast, incretins (hormones produced by the gastrointestinal tract and released into the gut in response to food intake) also potentiate insulin secretion and sensitivity in their target tissues by playing an important role in pancreatic β-cell modulation [12] . However, this hormone is rapidly degraded by an enzyme called Dipeptidil Peptidase (DPP4).…”
Section: Obesity and Metabolic Syndromementioning
confidence: 99%